PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS OPEN ENDED UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Ayu, Wilza; Mujahidawati, Mujahidawati; Falani, Ilham (EMTEKA: Jurnal Pendidikan Matematika, 2024)
The development of advances in science and technology has a significant impact on the world of education, especially learning media. With the development of existing technology, we should be able to use it well to overcome various problems, especially in the field of education. One form of utilizing technology in the field of education is the use of video media as a learning aid in the classroom. Therefore, the purpose of this study is to determine the quality of Open Ended-based learning videos to improve students' ability to understand mathematical concepts based on valid, practical and effective criteria. The research method used is Reseacrh and Develompent with 4D Model (Define, Design, Development, Disseminate). The results obtained in this study are (1) the learning videos developed are valid with an assessment by material experts is 88.75% (very valid) and design experts are 72.30% (valid); (2) the learning videos developed are very practical with an assessment from the teacher of 96% and by students of 91.45; (3) The learning video developed effectively with the percentage of student response questionnaire assessment is 80% and based on the results of the ability test to understand mathematical concepts, 33 students have increased their abilities with medium or high criteria and have an average n-gain of 0.64 with moderate criteria.